Mobile Learning to Improve Student Learning Outcomes in Tennis - Septian Raibowo; Tono Sugihartono; Andes Permadi; Dian Pujianto (Indonesian Journal of Physical Education and Sport Science)
Studi purpose. The purpose of this study was to improve the learning outcomes of physical education students in learning tennis